Democratization and mature elections a study of youth political participation in voters 18 and automatic voter registration - Irma Wani Othman; Mohd Azri Ibrahim; Mohd Sohaimi Esa (Global Academic Excellence, 2022)
The discussion in this paper pertains to the issue of Voters 18 and Automatic Voter Registration (AVR). The issues refined in this debate include: (1) The efforts of democratization that is mature, fair, and equitable elections to advance social and political development; (2) Studies on the impact of youth political participation in the General Election (GE); (3) Justification of the enforcement & implementation of Vote 18; (4) Improvisation of the work of the election series; and (5) Jurisdiction and responsibility of the Election Commission (EC). This paper uses secondary sources, such as research results published in journals, scholarly writing, online news sources, and public forums, to employ a qualitative methodology. The results of the study indicate that the participation of 18-year-old voters is an important factor in the formation of a government capable of representing the interests of all age groups and the community as a whole. It is hoped that the young generation or youth will now exercise their rights with maturity, discernment, and efficiency. Voting is a personal decision, and there is no incorrect vote, but all young Malaysians should have the right to vote. The future of the nation can be influenced by the rationale behind efforts to involve the youth in political power determination. Thus, the elaboration research of this study should concentrate on the significance of political system, state government, and the federal constitution education for the young generation in order to prepare them to participate in general elections.